Development of Phet Simulation-Assisted Inquiry Model Learning in Elasticity Materials - Yuliana Yuliana; Wahyudi Wahyudi; Aris Doyan; Chester Ian S. Pineda (Postgraduate, University of Mataram, 2021)
This research aims to produce Phet simulation-assisted guided inquiry model learning devices on valid, effective, and practical elasticity materials. This research uses research and development (R&D methods with research models developed are 4D Models consisting of Define, design, development, and disseminate stage. Products from research in the form of syllabus, Learning Implementation Plan, Student Worksheet, and Instrument Learning Results Test. The results showed that 1) the validity results of the six validators using content validity ratio (CVR) and Content Validity Index (CVI) calculations showed a value of 1 (very valid) for all developed products, 2) teacher and learner responses to learning referring to the guided incubation learning model assisted by Phet simulation is very practical, as well as 3) guided incubation learning model-assisted Phet simulation is effectively used in learning. From the results of the study, it can be concluded that the development of learning devices is valid, effective, and practical